WLAN IMPLEMENTATION AND PERFORMANCE ANALYSIS - YEOP IBRAHIM, SHAKINAH (Universiti Teknologi PETRONAS, 2007)
Wireless networks are fast becoming ubiquitous in today's highly networked world. New applications based on 802.11 standards are rapidly expanding into corporate, residential, Wireless-Internet-Service-Provider (WISP), and hot-spot applications. With the advent of WLAN technologies, users are increasingly demand for WLAN high performance. Hence, the main focus of this project is to study, observe and experiment the WLAN implementation and performance analysis. The WLAN implementation and performance characteristics are firstly studied and several experiments are conducted. Two major applications are also performed under the wireless network condition that are File Transfer Protocol (FTP) and video streaming. The results show that the WLAN performance depends on location factors, network load and signal strength. The client location will affect the performance of interbuilding WLAN file transfer process. The media streaming performance can degrade significantly by signal quality.